SEPARATION OF PENICILLIN G FROM FERMENTATION BROTH BY EMULSION LIQUID MEMBRANE TECHNIQUE - Imam Santoso; Bachri Amran; Apriliana Laily Fitri (Universitas Gadjah Mada, 2010)
The separation of penicillin G from fermentation broth can be done by emulsion liquid membrane technique. The aim of this research is to establish the optimal conditions for the extraction and separation of penicillin G using emulsion liquid membrane technique. The optimal conditions were found to be at ratio of internal phase volume to membrane phase volume of 1:1 ; time of making emulsion, 1 min ; emulsion contact rate, 300 rpm; rate of stirring of emulsion, 2000 rpm ; rest time of emulsion, 13 min; concentration of penicillin G as external phase, 375 ppm; and concentration of surfactant, 5% (v/v). pH of internal phase is 8; pH of external phase 5; ratio of emulsion phase volume to external phase volume, 1:2 and concentration of carrier 2 mM. The concentration of penicillin G and phenylacetic acid from fermentation results were 24771 mg/L and 32675 mg/L. Extraction by emulsion liquid membrane technique gave the percentage of penicillin G 53.38% and phenylacetic acid 60.41%. The percentage phenylacetic acid which is still higher (60.41%) indicated that the penicillin G could not completely be separated from phenylacetic acid by emulsion liquid membrane technique.